A Sociolinguistic Study of Diglossia in the Film Ayat-Ayat Cinta 1: The Interaction of Fusha and ’Amiyah Languages in the Characters’ Dialogue - Indiana, Dinda Prema Ayu (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the phenomenon of diglossia in the film Ayat-Ayat Cinta 1 through a sociolinguistic analysis of the use of Fusha and ‘Amiyah Arabic in the characters’ dialogues. The study aims to identify the forms of Fusha and ‘Amiyah usage, the interaction between the two, and the social factors influencing language choice in the film. The method used is descriptive qualitative research employing the observe-and-record technique on the characters’ dialogues. The results indicate that Fusha is used in formal, religious, and academic contexts, while ‘Amiyah is used in everyday communication and informal settings. This study also found a shift in language use between Fusha and ‘Amiyah, indicating a continuum of diglossia in character interactions. Furthermore, language use is influenced by factors such as the communication situation, religious context, educational background, and the speaker’s diglossic competence. Thus, this film represents the relationship between language, culture, and the social life of Arab society.